2021
DOI: 10.1002/ps.6583
|View full text |Cite
|
Sign up to set email alerts
|

Spinosad resistance in field populations of melon fly, Zeugodacus cucurbitae (Coquillett), in Hawaii

Abstract: BACKGROUND: Control of Zeugodacus cucurbitae, a serious agricultural pest worldwide, often includes or is dependent on the use of spinosad-based insecticides. This is especially the case in Hawaii, where GF-120, a protein bait containing spinosad as the active ingredient, has been in use as a key integrated pest management (IPM) tool against this Tephritid for the last two decades. Here, we report on resistance to spinosad [resistance ratios (RRs) and median lethal concentration (LC 50 )] in Hawaii's populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…32,33 Hence, alternatives such as spinosad-targeted nAChRs have recently been used to control Tephritidae pests including B. dorsalis worldwide. 34,35 Identification and characterization of nAChRs subunit is crucial for acknowledging their interaction with insecticides targeting nAChRs and eventually providing support for resistance management of B. dorsalis. In the present study, full-length nAChRs β1 cDNA (named Bdorβ1) from B. dorsalis was isolated and characterized based on the transcriptome data.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Hence, alternatives such as spinosad-targeted nAChRs have recently been used to control Tephritidae pests including B. dorsalis worldwide. 34,35 Identification and characterization of nAChRs subunit is crucial for acknowledging their interaction with insecticides targeting nAChRs and eventually providing support for resistance management of B. dorsalis. In the present study, full-length nAChRs β1 cDNA (named Bdorβ1) from B. dorsalis was isolated and characterized based on the transcriptome data.…”
Section: Introductionmentioning
confidence: 99%
“…However, lab-selected spinosad-resistant Z. cucurbitae (RR = 35.79) exhibited resistance to beta-cypermethrin (RR = 11) and low level resistance to avermectin (RR = 5.45) and no cross-resistance to trichlorfon and fipronil [ 48 ]. Our field sites on Maui was in very close proximity to where spinosad resistance (RR = 8.5) was detected in 2017 [ 17 ]. Resistance in that Maui population reverted to susceptibility within 6 generations in the absence of spinosad exposure in the lab.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous year-round use of GF-120 has placed high selection pressure on Z. cucurbitae populations. A survey of spinosad resistance conducted in Hawaii in 2017 revealed up to 300-fold higher resistance to spinosad in melon fly populations collected from commercial farms on Oahu compared to a susceptible lab population [ 17 ]. The resampling of one of the Oahu populations one year after cessation of GF-120 use revealed that resistance persisted, albeit at a lower level (25-fold) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations